Nivel de capacitación del personal en la Farmacia Comunitarias ubicada en la ciudad de Babahoyo sector la PJ - Zumba Ormaza, Marco Aurelio (2020)
This case study, data from the description and analysis of the performance of the Sumedical Community Pharmacy staff, is an organization dedicated to the supply of pharmaceutical products and products aimed at people's health based on previous knowledge that the collaborators have acquired before of selling to your clients or potential clients and training them. Within the development of the same, the variety of problems within the framework of activities carried out by each employee, in their tasks within the working day, considering that it is a profit-making company with individual and collective benefits was considered. This analysis is approached in a neutral way, identifying all the variables that affect workers prior to entering the institution, considering that they have been in the city for some years. The information was collected through finds directed towards the workers, and documents of the organization as a means of sustenance and thus know with certainty, the problems that emerge and the causes that can have an impact on the sales of a whole day, or working day.